Packing Parameters of Bloom Graph - D. Antony Xavier; S. Kulandai Therese; Andrew Arokiaraj; Elizabeth Thomas (International Journal of Mathematics And its Applications, 2016)
Packing in graphs is an effective tool as it has lots of applications in applied sciences. In this paper, we determine the maximum H-packing for bloom graph in algorithmic manner with distinct vertices when H is isomorphic to P_3. Moreover we discuss the maximum F-packing for bloom graph with distinct vertices and disjoint edges when F is isomorphic to a family of cycles.